Association of two genomic variants with HPV type-specific risk of cervical cancer - Seifert, Finja; Eisenblätter, Rieke; Beckmann, Julia; Schürmann, Peter; Hanel, Patricia; Jentschke, Matthias; Böhmer, Gerd; Strauß, Hans Georg; Hirchenhain, Christine; Schmidmayr, Monika; Müller, Florian; Fasching, Peter; et al. (Tumour Virus Research, 2023)
Problem: Human papillomavirus infection is integral to developing invasive cervical cancer in the majority of patients. In a recent genome-wide association study, rs9357152 and rs4243652 have been associated with seropositivity for HPV16 or HPV18, respectively. It is unknown whether these variants also associate with cervical cancer triggered by either HPV16 or HPV18. Methods: We investigate whether the two HPV susceptibility variants show association with type-specific cervical cancer in a genetic case-control study with cases stratified by HPV16 or HPV18, respectively. We further tested whether rs9357152 modulates gene expression of any of 36 genes at the human leukocyte antigen locus in 256 cervical tissues. Results: rs9357152 was associated with invasive HPV16-positive cervical cancer (OR 1.33, 95%CI 1.03–1.70, p = 0.03), and rs4243652 was associated with HPV18-positive adenocarcinomas (OR 2.96, 95%CI 1.18–7.41, p = 0.02). These associations remained borderline significant after testing against different sets of controls. rs9357152 was found to be an eQTL for HLA-DRB1 in HPV-positive cervical tissues (pANOVA = 0.0009), with the risk allele lowering mRNA levels. Conclusions: We find evidence that HPV seropositivity variants at chromosome 6 and 14 may modulate type-specific cervical cancer risk. rs9357152 may exert its effect through regulating HLA-DRB1 induction in the presence of HPV. In regard of multiple testing, these results need to be confirmed in larger studies.
CRIS-Team Scopus Importer:2023-08-11
Keywords: Association study; eQTL; HPV infection; Human leukocyte antigen; Single nucleotide polymorphism; VASH1